اتجاهات تلاميذ المرحلة الابتدائية نحو مشروع ألعاب القوى للأطفال (kid’s athletics) من وجهة نظر أعضاء الرابطة الولائية للرياضة المدرسية لولاية المسيلة - دراسة ميدانية على مستوى الرابطة الولائية للرياضة المدرسية بولاية المسيلة - بوسعدية, جبار (My University, 2021)
عنوان الدراسة: اتجاهات تلاميذ المرحلة الابتدائية نحو مشروع ألعاب القوى للأطفال (kid’s athletics) من وجهة نظر أعضاء الرابطة الولائية للرياضة المدرسية لولاية المسيلة. هدف الدراسة: هدفنا من خلال هذه الدراسة الة معرفة اتجاهات التلاميذ نحو برنامج العاب القوى للأطفال في المرحة الابتدائية من خلال الوقوف على ثلاث أنواع من الاتجاهات (العاطفية، المعرفية، السلوكية) الفرضية العامة: • هناك مستوى متوسط لاتجاهات تلاميذ المرحلة الابتدائية نحو مشروع ألعاب القوى للأطفال (kid’s athletics) من وجهة نظر أعضاء الرابطة الولائية للرياضة المدرسية لولاية المسيلة؟ الفرضيات الجزئية: • يوجد مستوى مرتفع للاتجاهات المعرفية لتلاميذ المرحلة الابتدائية نحو رياضة الكيدس من وجهة نظر الاساتذة المطبقين (برنامج مطبق من طرف الرابطة الولائية الرياضة المدرسية لولاية المسيلة) • يوجد مستوى مرتفع للاتجاهات العاطفية لتلاميذ المرحلة الابتدائية نحو رياضة الكيدس من وجهة نظر الاساتذة المطبقين (برنامج مطبق من طرف الرابطة الولائية الرياضة المدرسية لولاية المسيلة) • يوجد مستوى مرتفع للاتجاهات السلوكية لتلاميذ المرحلة الابتدائية نحو رياضة الكيدس من وجهة نظر الاساتذة المطبقين (برنامج مطبق من طرف الرابطة الولائية الرياضة المدرسية لولاية المسيلة) المنهج المتبع: قمنا باتباع المنهج الوصفي لملائمته طبيعة دراستنا. أدوات الدراسة: قمنا بتصميم استمارة استبيان، وقد احتوت على (27). - جاء هذا البحث في جوانب وفصول: الفصل الأول: الإطار العام للدراسة من مقدمة واشكالية، فرضيات الدراسة واهمية واهداف ومصطلحات الدراسة. الجانب النظري وقسم على ثلاث فصول: وتناول الفصل الثاني: الاتجاهات أما الفصل الثالث: ألعاب قوى الاطفال الفصل الرابع: مرحلة التعليم الابتدائي الجانب التطبيقي وقسم على فصلين: تطرقنا في الفصل الخامس: للإجراءات المنهجية في الدراسة اما الفصل السادس فتم فيه: عرض النتائج وتفسيرها ومناقشتها - من أهم النتائج التي توصل إليها الباحث - يوجد مستوى مرتفع للاتجاهات المعرفية لتلاميذ المرحلة الابتدائية نحو رياضة الكيدس من وجهة نظر الاساتذة المطبقين (برنامج مطبق من طرف الرابطة الولائية الرياضة المدرسية لولاية المسيلة) - يوجد مستوى مرتفع للاتجاهات العاطفية لتلاميذ المرحلة الابتدائية نحو رياضة الكيدس من وجهة نظر الاساتذة المطبقين (برنامج مطبق من طرف الرابطة الولائية الرياضة المدرسية لولاية المسيلة) - يوجد مستوى مرتفع للاتجاهات السلوكية لتلاميذ المرحلة الابتدائية نحو رياضة الكيدس من وجهة نظر الاساتذة المطبقين (برنامج مطبق من طرف الرابطة الولائية الرياضة المدرسية لولاية المسيلة) - هناك مستوى مرتفع لاتجاهات تلاميذ المرحلة الابتدائية نحو مشروع ألعاب القوى للأطفال (kid’s athletics) من وجهة نظر أعضاء الرابطة الولائية للرياضة المدرسية لولاية المسيلة - توصل الباحث للعديد من التوصيات أهمها: - ادراج مشروع ألعاب القوى للأطفال في منهاج مادة التربية البدنية والرياضية في المرحلة الابتدائية. - اسناد مهمة تطبيق مادة التربية البدنية والرياضية عموما ومشروع العاب القوى للأطفال على وجه الخصوص للأستاذ مختص في النشاط البدني الرياضي التربوي. - ربط مشروع ألعاب القوى للأطفال بجانب انتقاء المواهب الشابة من المدارس وتوجيههم نحو الأنشطة المناسبة لتكوين كفاءات مستقبلية في ألعاب القوى للكبار. - ضرورة توفير المساحات الرياضية والوسائل البيداغوجية اللازمة لتطبيق مشروع ألعاب القوى الأطفال على أكمل وجه في المدارس الابتدائية. Study title: Attitudes of primary school students towards the children's athletics project from the point of view of members of the State Association of School Sports in the State of M'sila. Aim of the study: Our aim through this study is to know the students’ attitudes towards the children’s athletics program in the primary stage by identifying three types of attitudes (emotional, cognitive, and behavioral). General premise: • There is an average level of primary school students' attitudes towards the kid's athletics project from the point of view of the members of the State Association of School Sports in the State of M'sila? Partial Hypotheses: • There is a high level of cognitive attitudes of primary school students towards the sport of kiddies from the point of view of the applied teachers (a program implemented by the State Association of School Sports in the State of M'sila) • There is a high level of the emotional attitudes of primary school students towards the sport of kiddies from the point of view of the applied teachers (a program implemented by the State Association of School Sports in the State of M'sila) • There is a high level of behavioral attitudes for primary school students towards the sport of kiddies from the point of view of the applied teachers (a program implemented by the State Association of School Sports in the State of M'sila) Approach: We followed the descriptive approach to suit the nature of our study. Study tools: We designed a questionnaire, which included (27). key words: - directione - Children's athletics Primary education stage This research came in aspects and chapters: The first chapter: the general framework of the study from the introduction and problematic, hypotheses of the study and the importance, objectives and terminology of the study. The theoretical part is divided into three chapters: -The second chapter deals with trends - The third chapter: Children's Athletics -Chapter Four: Primary Education Stage The practical side is divided into two chapters: -In Chapter Five, we discussed the methodological procedures in the study -As for the sixth chapter, the results were presented, interpreted and discussed One of the most important findings of the researcher: - There is a high level of cognitive attitudes for primary school students towards the sport of kiddies from the point of view of the applied teachers (a program implemented by the State Association of School Sports in the State of M'Sila) - There is a high level of the emotional attitudes of primary school students towards the sport of kiddies from the point of view of the applied teachers (a program implemented by the State Association of School Sports in the State of M'Sila) - There is a high level of behavioral attitudes for primary school students towards kiddies from the teachers’ point of view (a program implemented by the State Association of School Sports in the State of M’sila) - There is a high level of primary school students’ attitudes towards the kid’s athletics project from the point of view of the members of the State Association of School Sports in the State of M’sila The researcher reached several recommendations, the most important of which are: The inclusion of the children's athletics project in the curriculum of physical education and sports in the primary stage. - Assigning the task of applying physical education and sports in general and the athletics project for children in particular to a professor specializing in educational sports physical activity. - Linking the children’s athletics project to the selection of young talents from schools and directing them towards appropriate activities to form future competencies in athletics for adults. - The necessity of providing sports spaces and pedagogical means necessary to implement the children's athletics project to the fullest in primary schools.
Keywords: الاتجاهات; ألعاب القوى الأطفال; مرحلة التعليم الابتدائي